Measured isotope activity ratios, calculated ages and monte-carlo derived age error, and Oxcal deposition model U-Th ages and associated age error of the stalagmite SIB-4 from Sibaki Cave, Southwestern Iran - Mojgan Soleimani; Alireza Nadimi; Gabriella Koltai; Yuri Dublyansky; Stacy A Carolin; Christoph Spötl (PANGAEA, 2023)
A total of 32 230Th ages were measured along the growth axis of SIB-4 stalagmite. 100-200 mg of calcite powder was drilled per sample in a laminar-flow hood following growth lamina. The samples were chemically prepared at the Department of Earth Sciences, University of Oxford. The samples were spiked with a mixed 229Th-236U spike, dissolved in HNO3 and refluxed on a hot-plate overnight for spike-sample equilibration. Chemical separation of U and Th was done following procedures adapted from Edwards et al. (1987). The separated U and Th fractions were analysed on a Nu Plasma multi-collector inductively coupled plasma mass spectrometer, following the procedure described in Carolin et al. (2019). Individual 230Th ages with their 95% confidence intervals were calculated using an in-house Monte Carlo script that incorporates chemical blank errors, analytical uncertainties and initial 230Th/232Th uncertainties. The initial 230Th/232Th (atomic ratio) is estimated to be between 0.5 to 10.8 ppm (uniform distribution), equivalent to an activity ratio of 0.1 to 2.0. This range encompasses both the bulk earth value (230Th/232Th activity = 0.82) and the median detritus value calculated in a collection of speleothem studies (230Th/232Th activity = 1.5) (Hellstrom, 2006). Notably, SIB-4 samples exhibit large 230Th/232Th, with 90% of samples showing 230Th/232Th activity greater than 1000. This is due to high U content and low detrital Th content of the stalagmite. Thus, the age corrections related to detrital contamination are small (median of just 4 years), which is much less than the overall age error of ca. 100 years (2s).
In: Soleimani, M et al. (2023): U/Th, age model and stable isotope data from the Last Glacial Maximum to the Early Holocene in Sibaki Cave, Southwestern Iran [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.955861